Using Google Trends to assess COVID-19 related web search behaviour in Arabian Peninsula - Aymane Ajbar; Mourad Boumaaza; Abdelhamid M Ajbar (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background The relatively small, populated countries (Bahrain, Kuwait, Oman, Qatar, and the United Arab Emirates) of the Arabian Peninsula have recorded high per-capita COVID-19 infection rates. These countries also have a high internet penetrance rate with a large Google share. Google Trends is a freely accessible online tool that allows the user to analyze trends in public Google searches during a given period and across a specified region. This paper investigates the use of this tool to study public awareness of COVID-19 in the selected countries. # Methods The information sought by the public in the selected countries was grouped into three categories: (i) Coronavirus search item, (ii) COVID-19 symptoms, and (iii) protection measures. Data from Google Trends were analyzed using Joinpoint software. This approach enabled searches with a meaningful trend to be delineated and allowed them to be ranked by order of importance. # Results Overall, public interest in COVID-19 was found to be associated with seven symptoms (fever, cough, sore throat, headache, loss of smell, shortness of breath, and chest pain), and four preventive measures (social distancing, quarantine, hand sanitizers, and masks). However, Google trends found some disparities between the studied countries. # Conclusions Despite its limitations, Google Trends can be useful in uncovering the major areas of public interest in COVID-19 for countries with high internet penetrance rates. Data from Google Trends could be used as part of a health communication strategy to identify information needs and establish appropriate communication strategies to tackle the pandemic.